Enzymatic mechanism of MlrB for catalyzing linearized microcystins by Sphingopyxis sp. USTB-05 - Teng, Junhui; Xu, Qianqian; Zhang, Haiyang; Yu, Ruipeng; Liu, Chao; Song, Meijie; Cao, Xiaoyu; Du, Xinyue; Tao, Suxuan; Yan, Hai (Frontiers in Microbiology, 2024)
Microcystins (MCs) are the most widespread cyanobacterial toxins in eutrophic water body. As high toxic intermediate metabolites, linearized MCs are further catalyzed by linearized microcystinase (MlrB) of Sphingopyxis sp. USTB-05. Here MlrB structure was studied by comprizing with a model representative of the penicillin-recognizing enzyme family via homology modeling. The key active sites of MlrB were predicted by molecular docking, and further verified by site-directed mutagenesis. A comprehensive enzymatic mechanism for linearized MCs biodegradation by MlrB was proposed: S77 transferred a proton to H307 to promote a nucleophilic attack on the peptide bond (Ala-Leu in MC-LR or Ala-Arg in MC-RR) of linearized MCs to form the amide intermediate. Then water was involved to break the peptide bond and produced the tetrapeptide as product. Meanwhile, four amino acid residues (K80, Y171, N173 and D245) acted synergistically to stabilize the substrate and intermediate transition states. This study firstly revealed the enzymatic mechanism of MlrB for biodegrading linearized MCs with both computer simulation and experimental verification.